2020
DOI: 10.26434/chemrxiv.13482594.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipophilicity and Click Reactivity Determine the Performance of Bioorthogonal Tetrazine Tools in Pretargeted in Vivo Chemistry

Abstract: <p>The development of highly selective and fast biocompatible reactions for ligation and cleavage has paved the way for new diagnostic and therapeutic applications of <i>in vivo</i> chemistry. The concept of bioorthogonal pretargeting has attracted considerable interest, in particular for the targeted delivery of radionuclides and drugs. In nuclear medicine, pretargeting can provide increased target-to-background ratios at early time-points compared to traditional approaches. This reduces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 39 publications
(10 reference statements)
4
41
0
Order By: Relevance
“…[19][20][21][22] From a clinical point of view, fluorine-18 is an almost ideal radionuclide for Positron-Emission-Tomography (PET). [23][24][25] Its unique decay characteristics give rise to high resolution PET images and result in acceptable levels of radiation burden. In addition, the half-life of 110 min also enables distribution from the production site to other research facilities and clinics, and allows, as such, for commercialization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22] From a clinical point of view, fluorine-18 is an almost ideal radionuclide for Positron-Emission-Tomography (PET). [23][24][25] Its unique decay characteristics give rise to high resolution PET images and result in acceptable levels of radiation burden. In addition, the half-life of 110 min also enables distribution from the production site to other research facilities and clinics, and allows, as such, for commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the half-life of 110 min also enables distribution from the production site to other research facilities and clinics, and allows, as such, for commercialization. [23][24][25] We have recently reported the first successful direct labeling of 18 F-Tzs with suitable reactivity for in vivo chemistry. 26 In another study, we identified key properties for Tzs to be used for pretargeted strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] The reason for this is that highly reactive mono-or bis-(hetero)aryl-substituted Tzs decompose under the harsh conditions used for standard nucleophilic 18 F-fluorination (SN2 or SNAr) approaches. [11,17,29] Only relatively base insensitive and less reactive Tzs could be radiolabeled, via an 18 F-aliphatic substitution (SN2) strategy. Radiochemical yields (RCYs) up to 18% were achieved.…”
mentioning
confidence: 99%
“…The mean tumor-to-blood ratio was 0.9, and thereby the specific uptake is similar to what was previously reported for other pretargeted imaging agents in the same tumor model. [11] In contrast, a mean tumor-to-muscle ratio of 10 was detected which in fact is significantly higher compared to what has previously been found for the "state-of-the-art" Tz-based imaging agents [ 18 F]22 and [ 64 Cu]Cu-NOTA-PEG7-H-Tzin a similar pretargeting set-up (LS174T bearing mice, using CC49-TCO 72h prior to tracer injection, similar imaging timeframes) (Figure 4C and D). [25,59] However, [ 18 F]21 showed a 3 to 5-fold lower tumor uptake compared to those imaging agents (Figure 4E).…”
mentioning
confidence: 99%